Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Kemampuan Pemahaman Konsep dan Kemampuan Pemecahan Masalah Matematika Siswa Kelas VIII SMP Negeri 10 Kota Bengkulu - Annie Rachmawati Nalman; Agus Susanta; Hanifah Hanifah (Departement of Mathematics Education, 2023)
This research is motivated by the ability of students' understanding of mathematical concepts and in solving mathematical problems is still relatively low. The type of research used is a quasi experiment (quasi experiment). This research was conducted at SMP Negeri 10 Bengkulu City with a population of class VIII students totaling 201 students. The research sample was students in class VIII.C as the control class which consisted of 28 students and class VIII.B as the experimental class which consisted of 28 students who were taken based on simple random sampling technique. The data processing used is the MANOVA (Multivariate Analysis of Variance) test. The results of the study can be concluded that: 1) There is a significant influence by using the Problem Based Learning learning model on students' conceptual understanding abilities of 58%. 2) There is a significant effect by using the Problem Based Learning learning model on students' mathematical problem solving abilities of 57.7%. 3) There is a significant effect using the Problem Based Learning learning model on students' conceptual comprehension skills and students' mathematical problem solving abilities of 13.3%, 4) Students' problem solving abilities are higher after applying the Problem Based Learning (PBL) Learning Model with an average the average ability to understand the concept of the experimental class: 89.43 and the control class: 72.43, 5) The ability to solve problems taught with the Problem Based Learning model is higher than that taught conventionally. The average problem solving ability of the experimental class was 81.36 and that of the control class was 71.54